2012
DOI: 10.1109/tvcg.2012.189
|View full text |Cite
|
Sign up to set email alerts
|

A User Study on Curved Edges in Graph Visualization

Abstract: Abstract-Recently there has been increasing research interest in displaying graphs with curved edges to produce more readable visualizations. While there are several automatic techniques, little has been done to evaluate their effectiveness empirically. In this paper we present two experiments studying the impact of edge curvature on graph readability. The goal is to understand the advantages and disadvantages of using curved edges for common graph tasks compared to straight line segments, which are the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
4
43
1
Order By: Relevance
“…al [19] also showed no performance difference between Lombardi and straightline drawings, although, contrary to our results, their participants demonstrated an overwhelming preference for straight-line graphs.…”
Section: Discussioncontrasting
confidence: 99%
“…al [19] also showed no performance difference between Lombardi and straightline drawings, although, contrary to our results, their participants demonstrated an overwhelming preference for straight-line graphs.…”
Section: Discussioncontrasting
confidence: 99%
“…They failed to obtain correct answers in maps using straight lines. This result is consistent with previous findings that overlapping or intersecting features may cause a decrease in task correctness [1,21]. Thus, maps using straight lines lead to a lower effectiveness than maps using curves.…”
Section: Comparison Between Straight Lines and Curvessupporting
confidence: 92%
“…As the results of finish time show (Table 3 and Figure 3), the maps using curved features to represent the flow direction were significantly less efficient, which is a result similar to the findings of previous studies [21,22]. In our experiment, finish time reflects the average time that participants used in determining the directions of flows, comparing the volumes of flows, and judging the correct answers in one task.…”
Section: Comparison Between Straight Lines and Curvessupporting
confidence: 87%
See 1 more Smart Citation
“…Löffler and Nöllenburg [25] showed that all outerpaths, i.e., outerplanar graphs whose weak dual is a path, have an outerplanar Lombardi drawing. In terms of the usability of Lombardi drawings, two independent user studies [27,32] examined the performance of Lombardi versus straight-line drawings for several graph reading tasks. While the study of Purchase et al [27] showed an advantage of straightline drawings for two out of three tasks, but aesthetic preference for Lombardi drawings, the study of Xu et al [32] did not show significant performance differences between the two types of drawings, but a strong aesthetic preference for straight-line drawings.…”
Section: Introductionmentioning
confidence: 99%